Psychosocial status and economic dependence for healthcare and nonhealthcare among elderly population in rural coastal Karnataka - Priyanka Dsouza Rent; Sudeep Kumar; Mackwin Kenwood Dmello; Jagannath Purushotham (Wolters Kluwer Medknow Publications, 2017)
Introduction: The elderly who will constitute 10% of the Indian population by 2021 face problems such as deteriorating healthcare status, loneliness, and economic constraints among others. All these factors together may affect the psychosocial status of the elderly and their health-seeking behavior. With this background, the current study tried to evaluate the psychosocial status, economic dependence for health and nonhealth expenses and awareness regarding geriatric welfare services (GWS) among elderly patients. Materials and Methods: The study was carried out among 599 men and women aged above 60 who visited rural healthcare centers in two districts of Karnataka during September-December 2016. A semi-structured interview schedule was administered by a trained medical professional after taking informed consent. Results: Majority of the respondents said that they had company at home, interacted with people outside home and that their advice was honored. About 75.8% of the respondents reported that they were either partially or completely financially dependent on someone else. The mean cost of hospitalization was reported to be Rs. 11,086. Majority of those hospitalized depended on their children to pay for healthcare (66.9%), whereas 16.9% had availed government insurance schemes and 14.6% paid out of pocket. Nearly 64.9% of the respondents were aware of the GWS while 32.6% had used them. Conclusion: The absence of financial risk pooling mechanisms and social support may cause elderly to forego treatment because of the need to pay for healthcare and further deteriorate their psychosocial status. Government initiatives to improve healthcare and social services to the elderly maybe advocated.